Addressing the overdose epidemic requires timely access to data to guide interventions. (1st September 2015) - Davis, Corey S.; Green, Traci C.; Zaller, Nickolas D.
Abstract: Fatal opioid overdose, the leading cause of injury death in the USA, is regularly described as an epidemic. The response to the overdose crisis, however, has largely failed to utilise many of the public health tools that have proven effective in combating epidemics. Chief among these is the systematic and timely use of data by public health officials to track outbreaks and effectively target interventions. This failure is particularly acute regarding data from prescription monitoring programmes, which are routinely used by clinicians and law enforcement agents, but often unavailable to health officials. We argue for a shift in emphasis and resources towards an evidence‐based public health approach to data use for overdose prevention. [Davis CS, Green TC, Zaller ND. Addressing the overdose epidemic requires timely access to data to guide interventions. Drug Alcohol Rev 2016;35:383–386]